Optimalisasi Pembelajaran Sejarah Dengan Materi Pertempuran 10 November 1945 Di Surabaya Menggunakan Media Wordwall Untuk Meningkatkan Keterlibatan Peserta Didik Di Kelas XI SMA Negeri 5 Madiun - Ummah, Bella Merly Farohmatul; Hartono, Yudi; Nurkholipah, Siti (LPPM Universitas Putera Batam, 2024)
Learning media is something that is very necessary to convey and receive the material being discussed. In this article, researchers develop a wordwall learning media that is based on an analysis of the needs and potential that exist at SMA Negeri 5 Madiun. The research method used was Classroom Action Research (PTK). The subjects in this research were class XI students at SMA Negeri 5 Madiun. Data collection instruments include observations and interviews with students. The wordwall media created by researchers contains material content about the Battle of 10 November 1945 in Surabaya. The aim of this research is to increase student involvement in learning history in the classroom. The research results show that the Wordwall media implemented with students is effective in increasing student involvement. The use of wordwall media significantly increases students' interest in learning history. Students revealed that the wordwall's interactive features support learning to be more interesting and enjoyable, and help students to deepen material about the battle of 10 November 1945 more easily. Observations also show an increase in student participation and involvement in learning activities. The implementation of Wordwall media not only helps students understand historical material in more depth, but also trains critical, logical and creative thinking skills. Based on the research results, it is hoped that Wordwall media can be used as an alternative in history learning to create a more interactive and enjoyable learning experience.